Stability of bioactive compounds and shelf life of resveratrol-enhanced peanuts - Sales, Jocelyn M.; Resurreccion, Anna V.A (2011)
Phenolic compounds including resveratrol, have antioxidant properties that delay aging and reduce the risk of cancer, cardiovascular and Alzheimer's diseases. Previously, we showed that combines ultrasound (US)-UV process enhanced resveratrol in peanuts better than US or UV alone, to levels 2.8 times greater than that in red wine, the major food source. This study aims to determine shelf life of roasted resveratrol peanuts-enhanced peanuts (REP) and to investigate the stability of trans-resveratrol (RES), total phenolics (TP) and trolox equivalent antioxidant capacity (TEAC) during storage. Raw peanuts were washed, sanitized, imbibed, sliced, processed, using optimum US-UV by exposing to US (70 mW/cm^3 power density for 10 min) followed by 50 min exposure at 40 cm distance from UV light (254 nm), incubated for 36 h at 25°C, dried, rosted, and packaged in polyethylene bags. Untreated samples were prepared as controls. Packages were stored at 30, 35, 40°C and at ambient, about 25°C. At pre-determined intervals, a total of six sampling times/temperature, samples were withdrawn from storage, and analyzed for RES, TP, TEAC, hexanal, descriptive sensory properties and consumer acceptance. Lipid oxidation, critical to REP's shelf life was due processing and storage effects. Initially, REP had higher hexanal and oxidized/off-flavors intensities but lower roasted peanutty flavor and overall acceptance (OA) than controls. During storage, oxidized/off-flavors increased as roasted peanutty flavor and OA decresed. REP's shelf life was 52 days at 25°C. Lipid oxidation in REP followed first order reaction with 0.02/day rate constant at 25°C, Q10 of 2.2, and activation energy of 300 cal/mol. At the end of shelf life trans-resveratrol, TP, and TEAC were reduced by 13, 8, and 27% to 3.29 μg/g, 1.76 mg GAE/g and 6.06 μMTE/g, respectively, sussgesting that trans-resveratrol and TP but not TEAC were stable in REP based on d"80% retained required during shelf life.
Keywords: Peanuts; Bioactive compounds; Antioxidants